(untitled) (LACCEI, 2024)
Peru is made up of three natural geographic regions. The high Andean areas of our country experience low temperatures every year, known as frost. On the coast, low temperatures are combined with high humidity. The direct effects are reflected in the respiratory system, also affecting the state of comfort. The purpose of this research is to provide a heating proposal in high Andean homes to achieve thermal comfort and to propose an alternative to the current global energy crisis, through a heating system, using residual energy from a kitchen to assist the social problem of extreme cold, all this with low cost and minimal environmental impact. Cold air will be captured from the house, through a duct, which will circulate through the kitchen. The heat emitted by the flame of the stoves will be used through the process of heat transfer by radiation and convection to heat the air flow. This will generate a temperature gradient, giving way to the thermosyphon phenomenon producing a continuous flow of hot air that is finally stored in a thermally insulated container and released to achieve thermal comfort in the house